The Concept of Reproductive Health Care and Abortion: A Small Survey in Turkey and Comparative Ethical Debate - Sahinoglu, Serap; Hanzade Dogan, H.; Ornek Buken, Nuket (Current Women's Health Reviews, 2013)
Objectives: The aim of this study is to deliberate the dynamics of reproductive health care, abortion and the role of nurses in Turkey in a comparative manner. Terms related to reproductive health have been highlighted in order to bring clarity to the conceptual framework of the topic. This topic has always been evaluated in Turkey from a legislative viewpoint and has not primarily been evaluated from the ethical viewpoint. Furthermore, majority of women in Turkey and all around the world might have not made free decision in certain circumstances. When it comes to practice, there are other factors to consider rather than the legal viewpoint such as women can often communicate better with nurses in the health care institutions than others. Methods: A small survey was carried out between September 2011 and December 2012. Initially, we prepared a questionnaire for nurses and we learned their attitudes to the topic. 50 nurses in Ankara in two big hospitals and 50 nurses in Istanbul in two big hospitals were interviewed and asked 11 questions about abortion and the female reproductive health care. Results: It was concluded that abortion has been used as a family planning tool. Women especially from rural areas have not been well educated about reproductive health care and when they have problems they have a tendency to leave the decision to men. Women in rural areas in Turkey cannot access health care service easily because of their socio-economic conditions. Nurses seem to be the center of communication with women in the health care service. Discussion: There is an ongoing debate about reproductive health care problems and abortion as ethical issues in today’s Turkey as well as in today’s globalizing world. Since culture dependent factors are crucially important, nurses should be well educated about cultural values, different attitudes, relevant ethical implications and behavioral reflections. Otherwise, techniques and strategies might be applied but without success or convincing results.
Keywords: nurses